2023
DOI: 10.3389/fimmu.2023.1174140
|View full text |Cite
|
Sign up to set email alerts
|

Paneth cell dysfunction in radiation injury and radio-mitigation by human α-defensin 5

Pradeep K. Shukla,
Roshan G. Rao,
Avtar S. Meena
et al.

Abstract: IntroductionThe mechanism underlying radiation-induced gut microbiota dysbiosis is undefined. This study examined the effect of radiation on the intestinal Paneth cell α-defensin expression and its impact on microbiota composition and mucosal tissue injury and evaluated the radio-mitigative effect of human α-defensin 5 (HD5).MethodsAdult mice were subjected to total body irradiation, and Paneth cell α-defensin expression was evaluated by measuring α-defensin mRNA by RT-PCR and α-defensin peptide levels by mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 76 publications
(84 reference statements)
1
2
0
Order By: Relevance
“…On the other hand, downregulation of antimicrobial proteins such as Defa20, Defa23, Defa29, and Dmbt1 was observed in the present study, which agrees well with a previous study that production of α-defensins is notably decreased by Paneth cells in a chronic alcoholic hepatitis mouse model . The decrease in the levels of α-defensins was linked to changes in the gut microbiota over time, enhanced gut permeability, and the presence of endotoxins . However, another important antimicrobial enzyme characteristic of Paneth cell–lysozyme did not change upon alcohol treatment, indicating that the Paneth cell population remains stable and the downregulation of defensins is unlikely a result of Paneth cell death.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand, downregulation of antimicrobial proteins such as Defa20, Defa23, Defa29, and Dmbt1 was observed in the present study, which agrees well with a previous study that production of α-defensins is notably decreased by Paneth cells in a chronic alcoholic hepatitis mouse model . The decrease in the levels of α-defensins was linked to changes in the gut microbiota over time, enhanced gut permeability, and the presence of endotoxins . However, another important antimicrobial enzyme characteristic of Paneth cell–lysozyme did not change upon alcohol treatment, indicating that the Paneth cell population remains stable and the downregulation of defensins is unlikely a result of Paneth cell death.…”
Section: Discussionsupporting
confidence: 92%
“… 6 The decrease in the levels of α-defensins was linked to changes in the gut microbiota over time, enhanced gut permeability, and the presence of endotoxins. 22 However, another important antimicrobial enzyme characteristic of Paneth cell–lysozyme did not change upon alcohol treatment, indicating that the Paneth cell population remains stable and the downregulation of defensins is unlikely a result of Paneth cell death. In villi, alcohol also upregulates proteins associated with lipid metabolism.…”
Section: Discussionmentioning
confidence: 96%
“…Wendler et al [ 83 ] demonstrated that reduced β-defensin 1 (hBD1 red ) was proteolytically degraded into different fragments, which exhibited increased antimicrobial activity and inhibited growth of Bifidobacterium breve . Nevertheless, oral administration of HD5 has been shown to provide therapeutic effects, as treatment with modified HD5 1–9 fragment D3 regulated appetite in obese mice [ 37 ], and oral administration of HD5 improved glucose tolerance [ 34 ], gut barrier function, and microbiota composition in mice after radiation-induced injury [ 84 ]. Similarly, intranasal treatment of hBD2 improved experimental asthma [ 85 ] and oral hBD2 administration ameliorated alcohol-associated liver disease in mice [ 40 ].…”
Section: Discussionmentioning
confidence: 99%